Creative Arts Students' Use of Social Media: Perspectives of Educators - Baboo, Shanthi Balraj; Lim , Jing Yi (School of Social Sciences, 2015)
The emergence of social media has made a tremendous change on lifestyle and communication practices in our society. Majority of the internet users today are hooked with social network sites in staying connected with people around the globe. New digital technologies and the social media also constantly change, changing communication and interaction between educators and learners. Social media enables the students and educators to be connected as it permits them to communicate on social media apart from the classroom setting. This paper explores the connections of educators and their students through social media as well as the perspectives of